Eksplorasi Peran Strategi Segmentasi, Targeting, Dan Positioning (STP) dalam Membentuk Perilaku Pembelian Konsumen Pada UMKM Kuliner - Ovan Krisadelman Zebua; Atika Zahra; Suci Destiyani; Farel Akbar Aditya Saragih; Kevin Valensius Siahaan; Cipta Kurnia; Sebrina Intan Aulia; Hendra Saputra (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
Culinary micro, small, and medium enterprises (MSMEs) in Indonesia face increasingly intense competition driven by shifting consumer preferences and rapid digital adoption. These dynamics highlight the need for a structured marketing approach. This study aims to examine how Segmentation, Targeting, and Positioning (STP) strategies shape consumer purchasing behavior among culinary MSMEs operating in urban areas. Using a descriptive qualitative design, data were obtained through semi-structured interviews with MSME owners and consumers, direct field observations, and supporting documentation. The analysis followed the interactive model of Miles and Huberman. The findings show that MSMEs predominantly apply geographic and behavioral segmentation, focusing on consumers residing near the business location and those who actively rely on digital platforms for food purchases. Targeting strategies are directed mainly toward millennials and Generation Z, who demonstrate strong digital engagement and high purchasing frequency. Product positioning emphasizes authentic taste and the use of local ingredients, which strengthen consumer perceptions of value and encourage repeat purchases. The study concludes that integrating STP with digital media enhances visibility, accelerates decision-making, and contributes to stronger consumer loyalty, making it a vital strategy for sustaining culinary MSMEs in a competitive marketplace.